The Virtual Workshop : An on-line adaptive resource for engineering and architecture : final report. - Prusty, Gangadhara; Vassar, Sasha; McCarthy, Tim; Ojeda, Roberto; White, Tim; Pearce, Garth; Smith, Warren; Mashiri, Fidelis; Doh, Jeung-Hwan; Uddin, Mohammad; Marcus, Nadine; Burton, Lorelle; et al. (Office for Learning and Teaching, 2017)
Final report from a project that developed state-of-the-art engineering and architectural design software tools to address key problems with current engineering and architectural design education. The tools were built around an adaptive tutorial concept. They help overcome the constraints of limited resources while providing students with improved and personalised support when they want it and where they want it. Whereas traditional engineering science courses and architecture courses solve cut-and-dried problems, engineering and architecture design courses serve up a scenario with imperfect input information and no predefined result, for which each student must devise their own solution. The tutorial assistance must therefore adapt to what each individual student devises and not undermine the authenticity of the design task by implying a single preferred outcome. A paradigm shift will be required for bringing the benefits of adaptive learning and teaching tools into engineering and architecture design courses.